Prediction of Hevea progeny performance in the presence of genotype-environment interaction - Goncalves, Paulo de Souza; Teixeira de Moraes, Mario Luiz [UNESP]; Silva, Marcelo de Almeida; Lima Gouvea, Ligia Regina; da Eira Aguiar, Adriano Tosoni; da Costa, Reginaldo Brito (Inst Tecnologia Parana, 2009)
Twenty two open-pollinated Hevea progenies from different parental clones of the Asian origin were tested at five sites in the Northwestern São Paulo State Brazil to investigate the progeny girth growth, rubber yield, bark thickness and plant height. Except for the rubber yield, the analysis of variance indicated highly significant (p<0.01) genotype x environment interaction and heterogeneity of regressions among the progenies. However, the regression stability analysis identified only a few interacting progenies which had regression coefficients significantly different from the expected value of one. The linear regressions of the progeny mean performance at each test on an environmental index (mean of all the progenies in each test) showed the general stability and adaptability of most selected Hevea progenies over the test environments. The few progenies which were responsive and high yielding on different test sites could be used to maximize the rubber cultivars productivity and to obtain the best use of the genetically improved stock under different environmental conditions.

Vinte e duas progênies de Hevea de polinização aberta obtidas de diferentes clones fenotipicamente selecionados de uma população de origem asiática Hevea brasiliensis (Willd. Adr. ex Juss.) Muell-Arg. durante três anos foram testadas em cinco locais. As variáveis perímetro do caule, produção de borracha, espessura da casca e a altura de planta foram determinadas em todos locais no Estado de São Paulo, Brasil. De acordo com as análises de variância, com exceção a produção de borracha, observou-se a existência de interações significativas entre genótipo x ambiente (p<0.01) e heterogeneidade de regressões entre as progênies. Porém, a análise de estabilidade de regressão identificou a interação de poucas progênies cujos coeficientes de regressão foram significativamente diferentes do valor esperado de um. Regressões lineares do desempenho médio das progênies para cada teste em um índice ambiental (média de todas as progênies em cada local) mostrou a estabilidade e adaptabilidade da grande maioria das progênies de Hevea nos diferentes locais. As poucas progênies que foram superiores e altamente produtivas nos diferentes testes de progênies podem ser utilizadas para maximizar a produtividade de cultivares de seringueira e determinar a melhor utilização do ganho genético dos grupos sob as diferentes condições ambientais de cultivo.
Keywords: Hevea brasiliensis; stability; adaptability; environmental index; linear regression